ASSOCIATION BETWEEN VITAMIN D AND GLAUCOMA: A SYSTEMATIC REVIEW - Valerie Gunawan, Alyssa Claudia; Caesari Putri, Aquirina; Stephanie Tandipayuk, Anggia Dwi; Atin, Fulgensius (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Glaucoma is a chronic progressive optic neuropathy that causes irreversible damage. Therefore, early diagnosis and appropriate treatment to control various risk factors associated with glaucoma are important. Risk factors associated with the development of glaucoma have been reported by many researchers and include both ocular and non-ocular (systemic) factors such as myopia, central corneal thickness, disc hemorrhage, and genetic factors. The aim: This study aims to show association vitamin D to glaucoma. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 89 articles, whereas the results of our search on SagePub brought up 98 articles. The results of the search conducted for the last year of 2013 yielded a total 13 articles for PubMed and 26 articles for SagePub. The result from title screening, a total 2 articles for PubMed and 18 articles for SagePub. In the end, we compiled a total of 10 papers. We included five research that met the criteria. Conclusion: Decreased serum 25-OHD concentration was associated with the presence but not the severity of POAG. It was suggested that Vitamin D deficiency should be considered a potential risk factor for the development of open-angle glaucoma.